Characteristic Composition of Guinea Fowl (Numida Meleagris) Egg - E.I. ADEYEYE (International Journal of Pharma and Bio Sciences, 2010)
The guinea fowl egg contains 83.3 % edible portion and has a total weight of 35.4 g. The edible portion contains a protein level of 85.5 % with amino acid profile better than that of whole hen’s egg. It is a good source of iron, has an amino acid index of 1.52 and predicted protein efficiency ratio of 3.21, total fatty acids of 6.74 g/100 g sample and utilizable energy due to protein of 49.3 %.